Transcatheter versus surgical aortic valve replacement: a systematic review and meta-analysis of randomised and non-randomised trials. Issue 1 (12th August 2014) - Nagaraja, Vinayak; Raval, Jwalant; Eslick, Guy D; Ong, Andrew T L
Abstract : Introduction: Many patients deemed inoperable for surgical aortic valve replacement (SAVR) have been treated successfully by transcatheter aortic-valve replacement (TAVR). This meta-analysis is designed to evaluate the performance of TAVR in comparison with SAVR. Methods: A systematic search was conducted using MEDLINE, PubMed, EMBASE, Current Contents Connect, the Cochrane library, Google Scholar, Science Direct and Web of Science. Original data were abstracted from each study and used to calculate a pooled OR and 95% CI. Results: Among three randomised controlled trials (RCTs), differences between the two cohorts were not statistically significant for the frequency of stroke (OR=1.94, 95% CI=0.813 to 4.633), incidence of myocardial infarction (MI), (OR=0.765, 95% CI=0.05 to 11.76) 30-day mortality rate, 1-year mortality rate (0.82, 95% CI=0.62 to 1.09) and acute kidney injury incidence rate. The non-RCTs demonstrated that the TAVR group had an amplified frequency aortic regurgitation at discharge (OR=5.465, 95% CI=3.441 to 8.680). While differences between the two cohorts were not statistically significant for the incidence of MI (OR=0.697, 95% CI=0.22 to 2.21), stroke (OR=0.575, 95% CI=0.263 to 1.259), acute renal failure requiring haemodialysis (OR=0.943, 95% CI=0.276 to 3.222), 30-day mortality (OR=0.869, 95% CI=0.621 to 1.216) and the need for a pacemaker (OR=1.832, 95% CI=0.869 to 3.862), a lower incidence of patients needing transfusion (OR=0.349, 95% CI=0.121 to 1.005) and new-onset atrial fibrillation (OR=0.296, 95% CI=0.124 to 0.706) was seen in the TAVR group. Conclusions: Randomised and observational evidence adjusted on the baseline patient's characteristics finds a similar risk for 30 days mortality, 1-year mortality, stroke, MI and acute kidney injury in TAVR and SAVR.